ANALISIS ALIH FUNGSI LAHAN KAWASAN HUTAN LINDUNG GUNUNG SEBATUNG DI DUSUN SASAPIT KECAMATAN PULAU LAUT UTARA KABUPATEN KOTABARU - Ilma Hadryanti; Suyanto Suyanto; Hafizianor Hafizianor (Jurnal Sylva Scienteae, 2020)
This research aims to analyze the biophysical and socio-economic culture as a consideration the possibility of evaluation the existence of settlement of Sasapit Backwoods in the area of Mount Sebatung Protected Forest. This research was Conducted by interview method to society. As respondents are the community of Sasapit backwoods which is administratively included the Tirawan village. The total number of households is only 38, then This research was conducted with 100% intensity (census). Biophysical conditions were observed based on secondary data in the form of climate data and thematic data. The results of this research indicate that the scores are 125 - 174, which means that the Sasapit backwoods area belongs to the category of limited production forest class and not protected forest. In addition, the results of interviews with the community of Sasapit backwoods, all the people do not want to be moved from the Sasapit backwoods.Keywords: Over land area function; protected forest; Sasapit Backwoods